A General, Activator‐Free Palladium‐Catalyzed Synthesis of Arylacetic and Benzoic Acids from Formic Acid. Issue 23 (8th May 2018) - Wang, Lin; Neumann, Helfried; Beller, Matthias
Abstract: A new catalyst for the carboxylative synthesis of arylacetic and benzoic acids using formic acid (HCOOH) as the CO surrogate was developed. In an improvement over previous work, CO is generated in situ without the need for any additional activators. Key to success was the use of a specific system consisting of palladium acetate and 1, 2‐bis((tert‐butyl(2‐pyridinyl)phosphinyl)methyl)benzene. The generality of this method is demonstrated by the synthesis of more than 30 carboxylic acids, including non‐steroidal anti‐inflammatory drugs (NSAIDs), under mild conditions in good yields. Abstract : Activator‐free carboxylation reactions of benzyl and aryl halides with simple formic acid are reported. Key to success was the use of a palladium bisphosphine complex, which both catalyzes the decomposition of formic acid and activates the C−X bond of the substrate.